Respuesta :

Answer:

(0, - 3) and (4, 5)

Step-by-step explanation:

Given the 2 equations

y = x² - 2x - 3 → (1)

y = 2x - 3 → (2)

Substitute y = x² - 2x - 3 into (2)

x² - 2x - 3 = 2x - 3 ← subtract 2x - 3 from both sides

x² - 4x = 0 ← in standard form

x(x - 4) = 0 ← in factored form

Equate each factor to zero and solve for x

x = 0

x - 4 = 0 ⇒ x = 4

Substitute these values into (2) for corresponding values of y

x = 0 → y = 2(0) - 3 = 0 - 3 = - 3 ⇒ (0, - 3 )

x = 4 → y = 2(4) - 3 = 8 - 3 = 5 ⇒ (4, 5 )